CHANGES IN PHYSICO-CHEMICAL TRAITS AND ENZYMES OXIDATIVE SYSTEM DURING COLD STORAGE OF ‘FORMOSA’ PAPAYA FRESH CUT FRUITS GROWN IN THE MEDITERRANEAN AREA (SICILY) - ADILETTA, G.; DI MATTEO, M.; ALBANESE, D.; FARINA, V.; CINQUANTA, L.; CORONA, O.; MAGRI, A.; PETRICCIONE, M. (Italian Journal of Food Science, 2020)
In this study, the effects of cold storage (5±0.5°C and relative humidity of 90±1%) on the quality of fresh papaya slices packed in a passive atmosphere with a semi-permeable film were evaluated. Physico-chemical traits such as total soluble solids, reducing sugar, pH increased during storage as well as the polyphenols, carotenoid content and antioxidant activity that reaching the highest values at end of trials. Changes in colorimetric parameters resulted in a significant decrease after 4 days of hue angle values, which then remained constant. The cutting process enhanced the antioxidant enzymes activity such as superoxide dismutase, catalase and ascorbate peroxidase. The analysis of the main components showed physical-chemical, qualitative, and enzymatic changes in papaya samples during cold storage, showing a shift from negative to positive values along the PC1 and indicating a qualitative decay of sliced papaya.